O livro digital como processo hipermidiático: a reconfiguração dos papéis do leitor, autor e editor no contexto dos usos e práticas editoriais - Almeida, Filipe Carvalho de (2015)
After a long journey using various materials from nature as learning support, books are presented in a new format: digital one. After living for more than 500 years with printed books, the mediated society comes across new practices and cyberspace provides necessary infrastructure to spread the electronic text, which has now personified immateriality. Thus, we have studied the concept of the book not only as an important means of acquiring knowledge, but also its use in contemporary times as a hypermedia process which involves various social actors and more broadly embraces the publishing sector. Our goal, therefore, is to study this process from the tripartite relationship between reader-author-publisher and the new practices and uses created by the advent of digital books as part of cyberculture. In order to do so, we have conducted an empirical qualitative research aiming at gathering current information about the growing adoption of eBooks in contemporary society and we have used the Grounded Theory in order to understand the current changes within the publishing sector. From the analysis we noticed that, despite the dynamics of production and distribution of digital books, the publishing market is still strongly based on business model for printed books. On the other hand, digital books have shown a potential that is capable of supplying new needs, which have risen in the cyberculture context, due more to the interaction and sharing media power than to its technology itself.